HUBUNGAN MATA KULIAH KEWIRAUSAHAAN DENGAN KESIAPAN BERWIRAUSAHA MAHASISWA PRODI PENDIDIKAN TEKNIK BANGUNAN FT UNP - Neno Octavia; Rijal Abdullah (Jurnal Applied Science in Civil Engineering, 2020)
This research is about the Relationship between Entrepreneurship courses and Student Entrepreneurship Readiness. The problem that arises in this research is the lack of readiness of FT UNP's Building Engineering Education Study Program students in entrepreneurship. This is because most students taking entrepreneurship courses only want to get grades and fulfill the requirements of lectures, so this affects students' desire to become entrepreneurial. This study aims to reveal the relationship between entrepreneurship courses and entrepreneurial readiness of students in the Building Engineering Education Study Program, FT UNP. This type of research is a descriptive correlational study using an instrument in the form of a questionnaire (questionnaire). The results of the correlation test obtained rcount of 0.776. This value is compared with the rtable at the 5% significance level of 0.2759. Then the results obtained rcount ≥ rtable, 0.776 ≥ 0.2759. Furthermore, the results of the significance test obtained tcount of 8.6122. This value is compared with the ttable at the 5% significance level of 2.00758. Then the results obtained tcount ≥ ttable, 8.6122 ≥ 2.00758. So it can be concluded that there is a significant relationship between entrepreneurship courses and entrepreneurial readiness of students of the Building Engineering Education Study Program FT UNP.